2008
DOI: 10.1080/00288230809510464
|View full text |Cite
|
Sign up to set email alerts
|

Sawdust and bark to treat nitrogen and faecal bacteria in winter stand‐off pads on a dairy farm

Abstract: New Zealand farmers are increasingly using improved management systems including moving animals out of paddocks to protect wet soils from damage during winter. The cows can be held for up to 20 h a day on specially constructed unroofed outdoor stand-off pads. Afield study was undertaken to investigate excreta nitrogen (N) transformations, N and faecal bacterial transport to drainage, and denitrification N losses when Pinus radiata bark or sawdust were used as filling materials in stand-off pads. About 3 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2009
2009
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 35 publications
(39 reference statements)
1
5
0
Order By: Relevance
“…This is in agreement with findings for coliform in the present study but in contrast to findings for E. coli and Enterococcus. However, E. coli removal rates similar to those achieved in the present study were reported by (Luo et al, 2008) who estimated that 90.2% of the E. coli originating in cattle manure were retained or inactivated in a bark pad and 99.7% in a sawdust pad. In addition, Vinten et al (2006) reported a 5-to 10-fold decrease in faecal indicator bacteria in effluent from woodchip corrals.…”
Section: Tablesupporting
confidence: 90%
“…This is in agreement with findings for coliform in the present study but in contrast to findings for E. coli and Enterococcus. However, E. coli removal rates similar to those achieved in the present study were reported by (Luo et al, 2008) who estimated that 90.2% of the E. coli originating in cattle manure were retained or inactivated in a bark pad and 99.7% in a sawdust pad. In addition, Vinten et al (2006) reported a 5-to 10-fold decrease in faecal indicator bacteria in effluent from woodchip corrals.…”
Section: Tablesupporting
confidence: 90%
“…On a similar study, Luo et al (2008) determined that sawdust and bark (from Pinus radiata) had no effect on nitrogen retention when used as bedding for dairy cows, and contrary to the finding of the former author, both woodchip media retained 96% of deposited excretal N and therefore nitrogen losses through leachate were minimal.…”
Section: Introductionmentioning
confidence: 68%
“…Studies that are available from trials investigating freedraining stand-off pads show contradictory results, and the leachate quality depends on a variety of factors, including stock density (Smith et al, 2010;Fenton, 2012), woodchip species (Ward et al, 2000(Ward et al, , 2001Molnar and Wright, 2006;Vinten et al, 2006;Luo et al, 2008), woodchip size (Shukla et al, 2002;Smith et al, 2010) and soil type (CREH, 2005;Camberato, 2007). Woodchips have been shown to absorb moisture and bind solids, and enable the formation of biofilms on woodchip particles that can assist in N-transformation processes, hence biologically treating leachate passing through the woodchip surface (Smith et al, 2010;Fenton, 2012).…”
Section: Wood Residues In Stand-off Padsmentioning
confidence: 99%
“…Woodchips have been shown to absorb moisture and bind solids, and enable the formation of biofilms on woodchip particles that can assist in N-transformation processes, hence biologically treating leachate passing through the woodchip surface (Smith et al, 2010;Fenton, 2012). Materials with a high cation exchange capacity (CEC) can be capable of retaining contaminant particles, including N as well as faecal bacteria (Luo et al, 2008), but research around processes at the woodchipsoil interface is scarce, and contaminant removal by bedding materials in stand-off pads needs further research (Fenton, 2012). However, leaching of environmental contaminants, such as N, P and faecal microorganisms, can be high-especially if such temporary pads are overstocked (Smith et al, 2010;Fenton, 2012) and/or located in areas with high rainfall or sandy soils (CREH, 2005).…”
Section: Wood Residues In Stand-off Padsmentioning
confidence: 99%